The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/obr.12996
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory‐based interventions targeting food craving: A systematic review and meta‐analysis

Abstract: Summary This systematic review and meta‐analysis aimed to quantify the effects of laboratory‐based interventions targeting specific mechanisms of food craving, to identify moderators of effects, and to qualitatively summarize findings. The study was conducted and reported according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Sixty‐nine studies were included in the quantitative synthesis, and separate meta‐analyses were conducted for the outcomes self‐reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 124 publications
1
10
0
Order By: Relevance
“…As expected, craving ratings were significantly reduced in LATER versus NOW trials independent of reward cue-type and smoking status. This result is consistent with previous research testing intentional down-regulation strategies to target craving for food (Wolz et al, 2020), cigarettes (e.g., Kober et al, 2010; Zhao et al, 2012), or emotions in general (Morawetz et al, 2017). The present study adds to these studies in that it provides a direct comparison of craving regulation between NS und TUD.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, craving ratings were significantly reduced in LATER versus NOW trials independent of reward cue-type and smoking status. This result is consistent with previous research testing intentional down-regulation strategies to target craving for food (Wolz et al, 2020), cigarettes (e.g., Kober et al, 2010; Zhao et al, 2012), or emotions in general (Morawetz et al, 2017). The present study adds to these studies in that it provides a direct comparison of craving regulation between NS und TUD.…”
Section: Discussionsupporting
confidence: 92%
“…This finding has important implications and suggests that COVID-19 dietary interventions should target improving craving control in people susceptible to increased HED sweet and savoury snack intake. Indeed, a meta-analysis of 69 laboratory based studies has shown that strategies such as imagining food cues and inhibitory control training reduces cravings and reduces food intake (Wolz, Nannt & Svaldi, 2020). It will be important for future studies to test whether such strategies are also effective for reducing intake for HED sweet and savoury foods during lockdowns.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that investigated the neurobiological basis of binge eating reported an enhanced attentional bias towards food stimuli, alterations in the reward system, and impairments in cognitive functions (e.g., poor inhibitory control skills towards food; Kessler et al [ 47 ], Smith et al [ 81 ]). Thus, Wolz et al [ 104 ] showed that training inhibitory control through behavioral inhibition might be effective in reducing subjective craving and food intake. Our first mediation model showed no significant direct link between exposure to social media and food craving.…”
Section: Discussionmentioning
confidence: 99%